Energy budget for postlarvae and juveniles of the malaysian prawn Macrobrachium rosenbergii De Man (Crustacea: Palaemonidae) - F Díaz-Herrera; G Juárez-Castro; E Pérez-Cruz; LF Bücke-Ramírez (Ciencias Marinas, 1992)
An experiment was conducted to determine the energy budget of postlarvae and juveniles of Macrobrachium rosenbergii fed with Bovilac Prawn and Purina Trout Chow. The specific dynamic effect was 4% and 7% greater for postlarvae and juveniles fed Purina. The values calculated for the scope for growth obtained for postlarval and juvenile prawns were 11.62% and 18.66% for organisms fed Purina Trout Chow (P < 0.05). Indicators of energetic substrate such as respiratory quotient, O:N atomic ratio and the rate of metabolic substrate, showed that the main substrates oxidized by the prawns were carbohydrates, followed by lipids and in less amount proteins. Since both prawn developmental stages used carbohydrates as the main substrate to meet their metabolic requirements, we can conclude that the highest percentage of proteins supplied by Purina Trout Chow was channelled into growth.